Almadrava: men and sea. Social relationship in a short-term community - Batista, Nuno Miguel (2018)
Introduction: Description of the relationship men/sea, on a specific social and life context, in a fishing community temporarily settled in Faro beach, during the tuna fishing period. It was discovered that such a fishing community existed for long decades in this place, where almost 200 families lived only during tuna’s fishing season. This community only had limited and rudimentary resources, based exclusively on human strength. Nevertheless, they developed their own rituals, beliefs and way of living. Now everything is almost extinct. Objective: Report the specificities of the spatial organization and socio-economic relations of this Armação, encouraging the generational continuity, the awareness of this disappeared heritage, its valorization and the awakening of collective memory. Methods: The participatory action and the qualitative methods were used, elaborating unstructured interviews, privileging the direct contact with those who lived in the Armação. The criteria used to select the interviewees consisted of lucidity, gender, social hierarchy and geographical origin. Results: Show the existence of a socioeconomic hierarchy that translated into a physical hierarchy; the registration and dissemination of the theme facilitates access to information. Conclusions: This paper is a remark to the authorities and stakeholders to preserve the collective memory and, an awakening of minds and consciences, influencing general society in the sense that it will be an alert to a value that, in general, has been lost and forgotten.